Thermodynamic Study of the Solubility of Naproxen in Some 2-Propanol + Water Mixtures (2023)
The equilibrium solubilities of the anti-inflammatory drug naproxen (NPX) in 2-propanol + water mixtures were determined at several temperatures from 298.15 to 313.15 K. The Gibbs energy, enthalpy, and entropy of solution and of mixing were obtained fro